Reconstructed Hierarchically Structured Keratin Fibers with Shape-Memory Features Based on Reversible Secondary-Structure Transformation - Xu, Xiaoyun (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.